(untitled) (Journal of Hama University, 2025)
The research aimed to determine the degree of student _ teachers’ practice the cooperative learning principles during the execution of practical education lessons. The two researchers used a descriptive approach and prepared an observation card. The search sample included (155) student _ teachers. The research results showed that: The student _ teachers practice the cooperative learning principles during the execution of practical education lessons to a medium degree, and that the work of one of the parents at least in the teaching profession raises the degree of the student _ teachers’ practice the cooperative learning principles, as well as following a course in the field of preparing teachers raises the degree of the student _ teachers’ practice the cooperative learning principles, and in light of the research results, the two researchers presented some recommendations.